IDENTIFICATION OF WORK BURNOUTS IN EDUCATION STAFF MERCU BUANA UNIVERSITY YOGYAKARTA - Palasara Brahmani Laras; Eka Aryani; Abdul Hadi (Jurnal Penelitian Bimbingan dan Konseling, 2021)
This study aims to identify the level of work burnout among educational staff at Mercu Buana University Yogyakarta. Apart from that, this research also identifies the things underlying the work burnout so that follow-up can be done regarding the results obtained. This research method is a survey method. The subjects of this study were all educational staff in the work unit at Mercu Buana University Yogyakarta. Data analysis was performed using a quantitative descriptive approach with percentage techniques. The results of this study indicate that the educational staff at Mercu Buana University Yogyakarta with a percentage value of 92.45% in the "Low" category and with a percentage value of 7.55% in the "Medium" category.Keywords: Work Burnout, Education Staff, Identify